Pedagogical Opportunities of Utilizing Motivational and Coaching Technologies in Managing the Labor Productivity of Teaching Staff - Askarov , Ilxomjon (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Systematic enhancement of pedagogical productivity dictates a definitive paradigm shift from conventional administrative oversight to advanced motivational and coaching frameworks. This empirical longitudinal study investigates the efficacy of integrating targeted coaching methodologies to optimize teaching performance within dynamic academic environments. Involving a stratified sample of 124 educators, the research comprehensively measured the impact of individualized coaching cycles on pedagogical output and emotional intelligence. Implementing a mixed-methods design, quantitative classroom engagement data and qualitative professional satisfaction metrics were analyzed. Statistical evaluation demonstrated a robust positive correlation (r = 0.78, p < 0.01) between structured coaching interventions and sustained academic productivity. Educators utilizing cognitive-behavioral coaching strategies exhibited enhanced resilience against professional burnout and higher adoption rates of progressive didactic techniques. Transforming the administrative role into a facilitative coaching dynamic dismantled rigid hierarchical barriers, fostering a collaborative culture of reflective practice. Evaluating these parameters unequivocally confirms modern educational management must prioritize psychological empowerment, establishing a highly replicable, data-driven model for systemic educational reform.